Pengaruh Persepsi Kualitas Produk, Citra Merek dan Persepsi Harga Terhadap Minat Beli pada Konsumen Produk Somethinc - Wandari Ambarwati; Sri Padmantyo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the influence of product quality perception, brand image, and price perception on purchase intention of Somethinc product consumers in Surakarta City. Data were collected through questionnaires using purposive sampling from 152 respondents aged 19–24 years. The instrument employed a 5-point Likert scale and was tested for validity and reliability. Multiple linear regression analysis was performed using SPSS 21. The results indicate that product quality perception, brand image, and price perception have a positive and significant effect on purchase intention, with price perception being the most dominant factor. Consumers rated the product quality and brand image as very good and the price as very affordable, which significantly influenced the high purchase intention for Somethinc products. This study contributes to understanding the factors affecting purchase intention in local beauty products.